QUYOSH BATARIYASINING SAMARADORLIGI VA BOSHQA PARAMETRLARGA ALOQADORLIGI - O’rinboyev, D.R.; Suvanov, A.X.; Suvanov, J.X. (SCIENCE and SOCIETY, 2022)
The efficiency of a-Si:H solar cell and its dependence on other parameters were studied. Formulas for calculating solar battery capacity, fill factor and VAX changes due to external influences were compared with experiments.